2014
DOI: 10.3947/ic.2014.46.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Clinical Outcomes of Acute Respiratory Virus Infection in Hospitalized Adults

Abstract: BackgroundEtiologies and clinical profiles of acute respiratory viral infections need to be clarified to improve preventive and therapeutic strategies.Materials and MethodsA retrospective observational study at a single, university-affiliated center was performed to evaluate the respiratory viral infection etiologies in children compared to that in adults and to document the clinical features of common viral infections for adults from July 2009 to April 2012.ResultsThe common viruses detected from children (2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
28
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 17 publications
7
28
2
5
Order By: Relevance
“…The assessment of the unadjusted differences in the frequency of symptoms and signs (Table and Table ) also showed few differences between the influenza viruses. Compared to influenza B, there was some evidence that patients with influenza A (not further specified) less often presented with myalgia (four studies—all focusing on children—of fifteen) were less often sent to the hospital for medical advice and/or further investigation (two studies of fourteen) and more often presented with cough (two studies of nine).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The assessment of the unadjusted differences in the frequency of symptoms and signs (Table and Table ) also showed few differences between the influenza viruses. Compared to influenza B, there was some evidence that patients with influenza A (not further specified) less often presented with myalgia (four studies—all focusing on children—of fifteen) were less often sent to the hospital for medical advice and/or further investigation (two studies of fourteen) and more often presented with cough (two studies of nine).…”
Section: Resultsmentioning
confidence: 89%
“…An overview of the studies (Table and Table ) showed a lot of diversity in the populations that were investigated: Studies are presented in terms of hospitalized patients (n = 22) or cover mainly outpatient settings (n = 19), such as primary care (n = 6) or community‐based (n = 4) settings. Most studies were carried out in Asia (n = 17), Europe (n = 15), or North America (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…In temperate countries, a higher prevalence of HMPV has been reported during the months of winter and spring, with a lower seasonality than HRSV213141516. Climate also plays an important role in determining the seasonality of HMPV in tropical countries.…”
mentioning
confidence: 99%
“…the LOS for patients infected with INF A was reported to be 6.9 days, whereas LOS for patients infected with ADV or hCoV OC43 was 8.2 days and 8.1 days, respectively [14]. In another study, RSV and hMPV infections reportedly resulted in LOS of 4 days and 3 days, respectively [15].…”
Section: Discussionmentioning
confidence: 97%